Synthesis and characterization of tenorite (CuO) nanoparticles from smelting furnace dust (SFD) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Tenorite (CuO) nanoparticles were prepared from a dilute CuSO4 solution. The solution was obtained by leaching (pH=1.5) of smelting furnace dust of Sarcheshmeh Copper Complex, Iran. The recovery of copper from the acidic sulphate solution was carried out by solvent extraction using Lix 984-N. Tenorite nanoparticles were synthesized by direct thermal decomposition of Langite [Cu4(OH)6SO4(H2O)2]as a precursor which was calcinated in air for 2 h at 750 °C. The Samples were characterized by X-ray diffraction, infrared spectroscopy, scanning electron microscopy, and transmission electron microscopy. The average diameter of the spherical pure CuO nanoparticles and their crystallite size were estimated to be 92 nm and 40 nm, respectively. The simplicity of the present method suggests its potential application at industrial scale as a cheap and convenient way to produce pure CuO nanoparticles from dilute CuSO4 solutions obtained from leaching of smelting furnace dust.